Barely Scratching the Surface: An Experimental Approach to Engraved Magdalenian Plaquettes - Matthew Amy (EXARC Journal, 2020)
This paper investigates the creation, utilisation, and destruction of engraved Magdalenian plaquettes through the application of actualistic experimental replication. Archaeological evidence suggests that there is a relationship between plaquettes and hearth structures, as well as engraved depictions and the destruction of the plaquettes through heating. However, this relationship between fire and plaquettes has not yet been tested using experimental archaeology. This paper focuses on understanding the relationship of the plaquettes with hearth construction, and how this stage of their object biography may relate to and inform the depictions produced. Further, the experiments presented here explored whether there was a practical benefit to utilising plaquettes in hearth construction, as well as the effects of heating within specific hearth configurations, informed by observed spatial patterning of plaquettes at Magdalenian sites. The results of these experiments showed that the stacking of plaquettes to form an oven-like hearth structure decreased fuel consumption by over 50% whilst still producing adequate directional heat. However, the heat modification exhibited on the experimental plaquettes did not match those of the archaeological examples, with very few experimental examples of cracking and colour change. The paper discusses some potential explanations for the disparity between experimental results and archaeological patterning.